2018
DOI: 10.1128/mcb.00110-18
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Alternative Oxidase Influences Jun N-Terminal Kinase Signaling and Cell Migration

Abstract: Downregulation of Jun N-terminal kinase (JNK) signaling inhibits cell migration in diverse model systems. In Drosophila pupal development, attenuated JNK signaling in the thoracic dorsal epithelium leads to defective midline closure, resulting in cleft thorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 120 publications
(136 reference statements)
1
13
0
Order By: Relevance
“…And the tumorigenesis potential of GBM CSCs was related to NDRG4 [24]. Moreover, the regulation of mitochondrial alternative oxidase expression could affect cell migration by changing of mitochondrial heat production [25]. The results of those researches were consistent with our primary hypothesis.…”
Section: Discussionsupporting
confidence: 83%
“…And the tumorigenesis potential of GBM CSCs was related to NDRG4 [24]. Moreover, the regulation of mitochondrial alternative oxidase expression could affect cell migration by changing of mitochondrial heat production [25]. The results of those researches were consistent with our primary hypothesis.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, two different lines of mice ubiquitously expressing AOX (El‐Khoury et al ; Szibor et al ) showed no significant deviations from controls, even when over 350 physiological, behavioral and metabolic parameters were measured. Nevertheless, AOX was able to confer protection against various kinds of physiological stress, ranging from exposure to respiratory poisons such as cyanide or antimycin A (Fernandez‐Ayala et al ; El‐Khoury et al ; Szibor et al ), genetically engineered OXPHOS deficiency (Kemppainen et al 2014; Rajendran et al ) pathological models related to oxidative, proteotoxic, nutritional, and proinflammatory stress (Fernandez‐Ayala et al ; Humphrey et al ; El‐Khoury et al ; Mills et al ; Giordano et al ), or disturbed nuclear‐receptor and Jun‐kinase signaling (Andjelković et al, ; Andjelković et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, AOX by-passes two proton pumps of the ETC, namely cIII and cIV [6,7], and represents a metabolic rescue mechanism that is absent in vertebrates [3]. Notwithstanding its natural absence, AOX can be xenotopically expressed in a catalytically active form in human cells with primary respiratory chain dysfunction [8] or mouse mtDNA-depleted cells [9], in drosophila disease models [10][11][12][13][14][15], and in the mouse [7,16] by using an AOX cDNA transiently expressed or integrated into specific sites in the genome. Remarkably, in most cases this has been achieved without producing adverse phenotypic effects, at least under standard physiological conditions, i.e., in the absence of metabolic stress signaling related to respiratory disruption [7].…”
Section: Introductionmentioning
confidence: 99%